2021
DOI: 10.3389/fnins.2021.766781
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Electroencephalogram Standardization: A Sex- and Age-Differentiated Normative Database

Abstract: We describe the utility of a standardized index (Z-score) in quantitative EEG (QEEG) capable of when referenced to a resting-state, sex- and age-differentiated QEEG normative database (ISB-NormDB). Our ISB-NormDB comprises data for 1,289 subjects (553 males, 736 females) ages 4.5 to 81 years that met strict normative data criteria. A de-noising process allowed stratification based on QEEG variability between normal healthy men and women at various age ranges. The ISB-NormDB data set that is stratified by sex p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 45 publications
1
18
0
Order By: Relevance
“…Brain functionalities are known to vary with gender and clearly degenerate with age. To account for this, our study utilized iMediSync, Inc’s normative database ISB-NormDB which holds EEG data of 1,289 healthy control subjects (553 males, 736 females) aged 4.5–81 years old ( Ko et al, 2021 ). The database provides standardized age- and sex-specific features referred to as Z-scores, which are common and statistically robust measures of variation from norms and capture standard deviation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Brain functionalities are known to vary with gender and clearly degenerate with age. To account for this, our study utilized iMediSync, Inc’s normative database ISB-NormDB which holds EEG data of 1,289 healthy control subjects (553 males, 736 females) aged 4.5–81 years old ( Ko et al, 2021 ). The database provides standardized age- and sex-specific features referred to as Z-scores, which are common and statistically robust measures of variation from norms and capture standard deviation.…”
Section: Methodsmentioning
confidence: 99%
“…The dataset was segregated into two groups, ADD and NADD. The NADD group consisted of subjective cognitive decline (SCD) and mild cognitive impairment (MCI) data, along with iMediSync, Inc.’s EEG data of healthy individuals from ISB-NormDB ( Ko et al, 2021 ). The inclusion of MCI data in the NADD group was crucial for the identification of significant ADD-specific characteristics that are not observed in the pre-clinical stage of ADD.…”
Section: Methodsmentioning
confidence: 99%
“…First, the power spectral density of the EEG rhythms was computed using Fast Fourier Transform (FFT) method with 0.25 Hz of frequency resolution using the iSyncBrain AI-driven autoanalysis system. Then, the signal was decomposed into the following frequency bands: delta (1-4 Hz), theta (4-8 Hz), alpha 1 (8-10 Hz), alpha 2 (10-12 Hz), beta 1 (12-15 Hz), beta 2 (15-20 Hz), beta 3 (20-30 Hz), and gamma (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45). For each channel and frequency band, the average power during the recording was calculated and treated as a feature.…”
Section: Feature Generationmentioning
confidence: 99%
“…ISB-NormDB is sex- and age-differentiated standardized QEEG normative database ( 11 ). ISB-NormDB has total 1,289 subjects’ QEEG data (553 men, 736 women, ages from 4.5 to 81 years).…”
Section: Eeg Analysismentioning
confidence: 99%
“…However, QEEG is user-independent data, which has lots of variability. Our previous study reported the sex- and age-differentiated standardized quantitative EEG (QEEG) normative database (ISB-NormDB), which can remove user-independent variability ( 11 ). Through this database and sex- and age-fitted model, band power data can be converted to sex- and age-matched standardized band power values (Z-scored band power).…”
Section: Introductionmentioning
confidence: 99%